Exporters, importers and two-way traders: The links between internationalization, skills and wage - Francesco Serti; Chiara Tomasi; Antonello Zanfei (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2008)
How do trade activities affect firms' employment and wages structures? Using firm level data on Italian manufacturing firms, this paper adds to the existing literature, by assessing how the degree of involvement in international trade impacts on workforce composition, earning levels and wage inequality. We differentiate firms involved in both trading activities - namely two-way traders - from firms that only export, and from those that only import. We show that two-way traders have a higher propensity to employ non-production workers, exhibit significant wage gaps, but also pay higher wages for both production and non production workers, relative to non internationalized firms and to firms which are involved only in either export or import. The paper also looks at how the wages and the skill structure of the trading firms change with the country of destination and origin and with the firms' sectoral and geographical diversification.
Keywords: F10; F16; J21; 330; heterogeneous firms; exports; imports; wage inequality; skills; Import; Export; Unternehmen; Produktivität; Humankapital; Lohnstruktur; Italien